Peniel Maiaweng's View on Divorce and Remarriage: An Exegetical Review From Matthew 19:9 - Chandra Wahyuni Irawati (RERUM: Journal of Biblical Practice, 2022)
There are different views on divorce and remarriage. First, agree to divorce and remarriage. Second, agreeing to divorce and not agreeing to remarriage. Third, do not approve of divorce and remarriage. One of the writers who also gave his views on this topic is Peniel Maiaweng. This paper will discuss the concept of divorce and remarriage through a theological exegetical approach, especially in the text of Matthew 19:9. Through these exegetical results, the author will also present a response to Peniel Maiaweng's views.   Ada berbagai pandangan yang berbeda mengenai perceraian dan pernikahan kembali. Pertama, menyetujui perceraian dan pernikahan kembali. Kedua, menyetujui perceraian dan tidak menyetujui pernikahan kembali. Ketiga, tidak menyetujui perceraian dan pernikahan Kembali. Salah satu penulis yang turut memberi pandangan mengenai topik tersebut adalah Peniel Maiaweng. Tulisan ini akan membahas konsep perceraian dan pernikahan kembali melalui pendekatan eksegetis teologis khususnya pada teks Matius 19:9. Melalui hasil eksegetis tersebut, penulis juga akan memaparkan respons terhadap pandangan Peniel Maiaweng.